Antimicrobial properties of plant extracts - Cosme-Silva, Leopoldo; Dal-Fabbro, Renan [UNESP]; Duarte Khoury, Rayana [UNESP]; Benetti, Francine; Quintino Trizzi, Juliana [UNESP]; Dezan Junior, Eloi [UNESP]; Emerenciano Bueno, Carlos Roberto [UNESP] (My University, 2020)
Oral diseases are a major health problem, with periodontal and caries among the most important infectious disease, which influence quality of life. The relationship between oral disease and oral microbiota is well stablished in literature, since more than 750 species are found in oral cavity. Regardless the number of new antibiotics introduced in the market in the last years by pharmacological industry, resistance that pathogenic microorganisms develop against antibiotics has increased. Due to side effects and drug resistance, researches around the globe have been looking for new antimicrobial agents or antimicrobial enhancers, such as those from herbal sources. Medicinal plants and byproducts are constantly indicated and used throughout the world in several areas of medicine and dentistry to induce favorable responses and to treat different diseases. Also, plants naturally produce secondary metabolites that can be used as antimicrobials. There are several ways of producing herbal extracts and retrieve the active compound, as well as different tests to be performed in order to assess the antimicrobial potential. This chapter will briefly discuss the main techniques used and highlight the main properties of some compounds present in plants such as Myracrodruon urundeuva, Curcumin, Green tea, Lemon grass, Chamomile, Aloe Vera, Cinnamon, Psidium, Citrus and Capsicum. Due to the huge variety of plants in the literature, it is impracticable to describe all extracts with antibacterial properties. Therefore, this chapter mentions some of the extracts with such properties, which may serve as an introduction to new research and new researchers.
Keywords: Antibacterial Agents; Ethnopharmacology; Medicinal Plants; Phytotherapy; Plant Extracts